Ypatingasis archyvas Maskvoje - Jegelevičius, Sigitas (Lietuvos istorijos studijos, 1996)
The author provides in his review general information on the former top-secret Special State Archive of the USSR. Its existence wasn't known even to the majority of the employees who were working in the system of the state archives at that time. This archive kept materials related to institutions of special purpose, informal organizations, or persons with certain political attitudes from Germany and other European countries. The depository of the archives seized in Europe only became available to researchers from 1990. In the nearest future, any access to the holdings of this archive will not be made easier.Information is provided on the volume of the archive and the composition of the holdings. Holdings of German origin prevail. It is stressed that the holdings of Polish origin are equally important for the researchers of Lithuanian history as the German ones. Now, that is, from 1992, this archive has been called the Russian Storage Centre of Historic-Documentary Collections.The author extensively presents the Lithuanian materials kept in this archive. First of all, the documents of the second department (reconnaissance) of the Polish Army General Staff, which are important to Lithuanian history, are presented: the structure of this holding, its volumes, contents, and character. This is the main part of the review, comprising 3/4 of the text. Some attention is given to the prospects of using the German holdings.